2015
DOI: 10.1373/clinchem.2015.240028
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exosomes in Breast Cancer

Abstract: BACKGROUND Although it has been long realized that eukaryotic cells release complex vesicular structures into their environment, only in recent years has it been established that these entities are not merely junk or debris, but that they are tailor-made specialized minimaps of their cell of origin and of both physiological and pathological relevance. These exosomes and microvesicles (ectosomes), collectively termed extracellular vesicles (EVs), are often defined and subgrouped first and fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 69 publications
3
69
0
Order By: Relevance
“…For the undigested cfDNA, cells might have some protective mechanism. Some studies have shown that cancer cells actively secrete cfDNA into the blood circulation in different forms, such as in exosomes, and the cfDNA inside these carriers could be protected from degradation [12, 14]. Our results also suggested that breast cancer cells in G1 phase secrete more exosomes.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…For the undigested cfDNA, cells might have some protective mechanism. Some studies have shown that cancer cells actively secrete cfDNA into the blood circulation in different forms, such as in exosomes, and the cfDNA inside these carriers could be protected from degradation [12, 14]. Our results also suggested that breast cancer cells in G1 phase secrete more exosomes.…”
Section: Discussionsupporting
confidence: 66%
“…For example, microRNAs in blood have important functions in tumorigenesis, metastasis and resistance [14]. However, there are very few reports on the effects of cfDNA on cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that dysregulation in this communication is involved in pathogenesis of cancer. It has been shown that exosomes play an important role in cancer cell invasion and metastasis, stem cell stimulation, angiogenesis, apoptosis, interaction with immune system cells, and drug resistance [102,103]. Hannafon et al reported selective encapsulation or elevated enrichment of certain microRNAs in exosomes release in the bloodstream of patients with breast cancer [104], and other studies have reported elevated CEA and CA 15-3 in the exosomes of such patients [103].…”
Section: Comparison With Other Biomarkersmentioning
confidence: 99%
“…Thus, exosomes and their contents may be used as novel potential biological markers for disease diagnosis and prognosis, as a vehicle for drug intervention and RNA interference therapy, or as a potential target for clinical treatment. For instance, exosomes play a functional role in myocardial remodeling (1), Alzheimer disease (AD) (2), breast cancer (3,4), and other cancers (5-7).…”
Section: Contextmentioning
confidence: 99%